Automated Cost and Customer Based Business Process Reengineering in the Service Sector - Stelling, Mark (Cranfield University, 2008)
The design of business processes often ignores detailed consideration of service cost. With competitive market pressure, this has become a key factor for the service sector. Along with cost, customer satisfaction is a driving force in all organisations these days. In an increasingly competitive marketplace, due to the current emphasis on service throughout the whole economy, businesses must fight to attract and retain their customers. The response time for modification, or reengineering, of existing processes and the creation of new processes is important in the service sector – this is usually required in a short period of time in order to respond to market and/or customer demand. Thus, there is a requirement for the automation of business process reengineering in order to facilitate this and to minimise response time. In order to address the above, the research carried out during this project involved the design and development of a framework to integrate an activity based cost estimating approach which takes into account probability of resource usage in variable processes, with an automated business process reengineering technique which incorporates an evolutionary computing (genetic algorithms) based optimisation module. Along with this, a novel methodology for detecting risk of negative impact on levels of customer satisfaction without the availability of customer related data has also been developed and integrated with the reengineering technique - cost reduction being the primary objective, but not at the expense of customer satisfaction. The overall aim is to automate the reengineering of business processes to as great an extent as possible in order to save potentially considerable human time and effort. The development of the automated framework also included the creation of a numeric process representation mechanism in order to enable quantitative analysis of complex business processes. The framework is implemented within a prototype software platform for expert validation.